ENHANCING STUDENTS WRITING SKILL TO WRITE DESCRIPTIVE TEXT USING PEER REVIEW AND FREE WRITING TECHNIQUES - Sartika, Dewi; Arriyani, Nurfisi (English Community Journal, 2020)
The main purpose of this study was to see whether the use of peer review and free writing techniques was effective in improving students’ writing achievement in learning English as a Foreign Language. A non-randomized control-group pretest-posttest design was used. Out of the tenth graders SMA YPI Tunas Bangsa Palembang, 60 students were taken as the sample. There were three groups, each of which consisted of 20 students. The data were collected by asking students to write a composition that was evaluated by using Conventional Standard Written English rubric containing six aspects namely content, organization, voice, word choice, sentence fluency, and conventions. The data obtained were analyzed using one-way ANOVA. The findings showed that the two techniques were effective in improving the students’ writing achievement because the students were guided to check their friends' work and were encouraged to elaborate more ideas that they wanted to write freely.